SYSTEM DESIGN OF CREDIT CARD APPLICATION FORM DISTRIBUTION BNI BNI 46 CARD CENTER IN WITH MICROSOFT ACCESS - Edi Agus Salim. D; Drs. Sunarto Usna, MMSI Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2005)
Information is felt more and more important especially in the submission of reports ontopical matters in an organization or company. For a company like BNI Card Center,which continues to grow, reporting information pendirtribusian credit card applicationform an effective and efficient are needed. Scientific writing is carried out through fieldresearch and direct interviews with the Card Center. Seeing the need for information byparties Card Center, then designed a new system of distributing reports. Hopefully,through this new system will assist the Branch Services Unit to resolve the problem ofinformation delays.Based on research that has been done, the writer suggested that the data processing,especially in the distribution report FAKK use such computerized using MicrosoftAccess as the attached program design. This will assist the Branch Services Unit inproviding information to the leadership more quickly and accurately.